A Juridical Analysis of the Neutrality Principle of State Civil Apparatus in Expressing Opinions on Social Media - Munajatin Nurur Rokhmah Lingga Utami; Poltak Siringo-ringo; Marudut Silitonga (International Journal of Science and Environment (IJSE), 2026)
The purpose of this research is to obtain a concrete understanding of the legal politics regulating the applicability of the principle of neutrality for Civil Servants in carrying out their duties and responsibilities. This neutrality is closely related to the expression of opinions through the use of social media. The study also emphasizes the utilization of social media by Civil Servants in a way that better ensures adherence to the principle of neutrality. The problems addressed in this thesis are: First, how is the legal politics concerning the neutrality of Civil Servants according to the prevailing laws and regulations? Second, how is the regulation of social media use by Civil Servants in expressing opinions that better guarantees the principle of neutrality? The research method employed is normative legal research, using statutory and conceptual approaches. The findings show that violations of Civil Servant neutrality in the use of social media are caused by several factors, namely the substance of legislation, the institutional structure of law enforcement, and societal culture. In addition, these issues are also linked to the prevailing legal politics. The regulation of social media use by Civil Servants in expressing opinions requires a systemic approach to realize the expected principle of neutrality. The enforcement of neutrality among Civil Servants depends not only on legal substance, but also on legal structure and legal culture. These three elements are interconnected and highly significant in strengthening the implementation of the principle of neutrality for Civil Servants.